Role of tomography in gas/solids flow measurement - Yang, W.Q; Liu, S (Flow measurement and instrumentation, 2000)
Gas/solids flow measurement presents many challenges to academics and engineers. Although this subject has been investigated for many years, it still remains a notorious task. The main difficulty is that all existing multi-phase flow meters are flow-regime-dependent and suffer from severe non-linearity problems. Industrial process tomography is based on measuring a subject, such as a gas/solids flow, from many different viewing angles and reconstructing cross-sectional distributions, i.e. tomographic images. From the images the flow regime can be identified, the solids fraction and velocity profiles be derived, and the volumetric flow rate be measured. This paper discusses these possibilities, in particular with electrical capacitance tomography (ECT). Some new results are presented.